The Influence of the Work Environment, Work Discipline, and Rewards on the Performance of Production Department Employees at PT. Supreme Food Rembang Regency - A. Fatkhul Khoiri; Dian Ayu Liana Dewi (LPPM Universitas Buddhi Dharma, 2024)
A person's performance greatly influences what the company wants to achieve. If the employee's performance is bad, it has a big influence on the company's development, namely the company's development will decrease, and vice versa, if the employee's performance is good, the company will experience an increase. Managing good performance so that the performance process can run well, you must also pay attention to several important things, one of which is the employee environment, employee discipline and rewards. This research aims to determine the influence of the work environment, work discipline and rewards on the performance of employees in the production department of PT. Supreme Food Rembang Regency. The data used in this research is subject data or primary data. The data source used in this research uses primary data sources. Data collection used a questionnaire in the form of statements totaling 44 questions. The research sample used a saturated sample, that is, the entire population was sampled, namely 58 employees in the production department of PT. Supreme Food Rembang Regency. The testing technique uses validity tests and reliability tests. Data analysis uses multiple linear regression analysis techniques. The research results stated that the work environment had a significant positive effect on employee performance, work discipline had a non-significant positive effect on employee performance, rewards had a significant positive effect on employee performance.